Use of the unique therapeutic project with people using and abusing substances: an experience report (Revista Científica Integrada, 2024)
The Singular Therapeutic Project (PTS) aims at a personalized treatment for the patient with a multidisciplinary approach. From this perspective, during the visits, in a therapeutic community in a coastal city in the state of São Paulo, the patient was discussed about his relationship of dependence on psychoactive substances, as well as his mourning for the death of his wife and other personal demands. On the other hand, their expectations regarding their future were worked on due to possible scenarios, given that the patient had a strong idealization of the theme. Thus, the overviews of the patient's psychological aspects were taken and discussed with the supervisors of the mental health discipline in order to make the PTS effective Objective: to promote the mental health of the patient in a therapeutic community and to apply the practice of the theory addressed in the discipline of primary mental health care. Method: is an experience report about a male patient from a therapeutic community on the coast of São Paulo, Brazil, in which anamnesis was used to obtain data, as well as a genogram and echomap. Results: the patient had an acknowledgment about his personal issues, drug addiction and coping with grief, as well as completed his treatment in the therapeutic community. Conclusion: The mental health promotion actions were closed with the patient, thus, in view of this report, we consider that more reports about therapeutic communities should be stimulated, in order to improve interventions and health promotion of this population.
Keywords: Mental Health; Therapeutic Community; Drug users; Illicit drugs; Primary Health Care